Suroboyo Bus Operational Risk Management System Using the Fmea (Failure Mode Effect Analysis) Method - Ichsandi, Mustar (Jurnal Indonesia Sosial Teknologi, 2024)
Suroboyo Bus Operational Risk Management System Using Fmea Method (Failure Mode Effect Analysis). Suroboyo Bus currently has several operational risks so efficient risk management planning is needed. The risk management planning mechanism used is Failure Mode and Effect Analysis (FMEA) with the hope of identifying the risks inherent in the operational business process of Suroboyo Bus. It can be seen from the survey results that 35% of the public want to add routes and 25% of the public want to add fleets. From the results of risk identification, 18 causes of the highest operational risks were obtained, including Driver absence, Minor damage or disruption to tyres, Major damage or disruption to facilities inside, Minor damage or disruption to facilities inside the bus, Traffic congestion around the bus stop, No plastic bottle checks, Damage or incomplete bus spare parts that were missed from the checking process, No helper at the passenger gathering point, Accidents on the way to the bus stop, Bus accidents, Major damage or disruption to the engine, Major damage or disruption to tyres, Unprinted receipts (out of stock), Unvalidated receipts, Lost receipts, Gears not in P position when parking at the Pool, No bus spare part checking process, accidents by cleaning staff, so SOPs, regulations, and budget policies are needed.